2007
DOI: 10.1371/journal.pone.0000716
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification System for the Actions of IRS Chemicals Traditionally Used For Malaria Control

Abstract: Knowledge of how mosquitoes respond to insecticides is of paramount importance in understanding how an insecticide functions to prevent disease transmission. A suite of laboratory assays was used to quantitatively characterize mosquito responses to toxic, contact irritant, and non-contact spatial repellent actions of standard insecticides. Highly replicated tests of these compounds over a range of concentrations proved that all were toxic, some were contact irritants, and even fewer were non-contact repellents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
247
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(255 citation statements)
references
References 8 publications
(8 reference statements)
6
247
0
Order By: Relevance
“…Such evidence of human health impact is a fundamental and essential component in the critical path of development of any vector control tool, [38][39][40][41] especially new paradigms such as SR. 4 If the crude estimate of protective efficacy shown here, about 52%, is verified in statistically robust cluster-randomized trials, this instrument of control would likely approximate that benefit associated with LLINs. 42 It is important to note this study was not intended to assess a practical method of delivery of a spatial repellent product in malaria control.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence of human health impact is a fundamental and essential component in the critical path of development of any vector control tool, [38][39][40][41] especially new paradigms such as SR. 4 If the crude estimate of protective efficacy shown here, about 52%, is verified in statistically robust cluster-randomized trials, this instrument of control would likely approximate that benefit associated with LLINs. 42 It is important to note this study was not intended to assess a practical method of delivery of a spatial repellent product in malaria control.…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in vaccine development, no effective and acceptable multi-valent vaccines are currently available against mosquito-borne diseases. The approach to combat these diseases largely relies on interruption of the disease transmission cycle by either destruction of the aquatic stages or by killing the adult mosquitoes using chemical insecticides [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural avoidance does not have the same importance as physiological resistance but may be considered to be a contributing factor, leading to the avoidance of lethal doses of an insecticide (Chandre et al, 2000;Grieco et al, 2007). This type of response can be further divided into direct contact excitation (sometimes referred to as "irritancy"), and non-contact spatial repellency when insects move away from the insecticide-treated area before making direct contact (Chareonviriyaphap et al, 1997;Grieco et al, 2007).…”
Section: Behavioural Avoidancementioning
confidence: 99%
“…To better approximate insect behaviour in natural field settings, numerous experiments have been made over many decades using specially constructed experimental huts (Smith, 1965;Rozendaal et al, 1989;Roberts and Alecrim, 1991;Bangs, 1999;Grieco et al, 2000Grieco et al, , 2007Polsomboon et al, 2008;Malaithong et al, 2010). Most experimental hut studies have been conducted to observe the behaviour of Anopheles mosquitoes; however, Grieco et al (2007) successfully demonstrated that chemical actions could be observed in experimental huts using Ae.…”
Section: Behavioural Avoidancementioning
confidence: 99%
See 1 more Smart Citation